2009
DOI: 10.1080/02701367.2009.10599550
|View full text |Cite
|
Sign up to set email alerts
|

Expected Values for Pedometer-Determined Physical Activity in Youth

Abstract: This review assembles pedometry literature focused on youth, with particular attention to expected values for habitual, school day, physical education class, recess, lunch break, out-of-school, weekend, and vacation activity. From 31 studies published since 1999, we constructed a youth habitual activity step-curve that indicates: (a) from ages 6 to 18 years, boys typically take more steps per day than girls; (b) for both sexes the youngest age groups appear to take fewer steps per day than those immediately ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
4
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 55 publications
6
41
4
1
Order By: Relevance
“…We should also consider promoting an increase of 3000 steps per day (Tudor-Locke et al, 2011b) as an appropriate, research-based goal to help reduce the risk of child overweight/obesity, regardless of whether or not a child reaches their sex-specific daily step count recommendation for achieving 60 minutes of moderate to vigorous physical activity. Similar to other research (Brusseau et al, 2011;Tudor-Locke et al, 2009), our study found a significant difference between the average step counts for boys and girls (p < 0.001), with boys achieving an average of 2136 more steps per day than girls. However, there were no significant differences between pedometer step counts on weekdays versus weekend days (p = 0.755).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We should also consider promoting an increase of 3000 steps per day (Tudor-Locke et al, 2011b) as an appropriate, research-based goal to help reduce the risk of child overweight/obesity, regardless of whether or not a child reaches their sex-specific daily step count recommendation for achieving 60 minutes of moderate to vigorous physical activity. Similar to other research (Brusseau et al, 2011;Tudor-Locke et al, 2009), our study found a significant difference between the average step counts for boys and girls (p < 0.001), with boys achieving an average of 2136 more steps per day than girls. However, there were no significant differences between pedometer step counts on weekdays versus weekend days (p = 0.755).…”
Section: Discussionsupporting
confidence: 91%
“…However, there were no significant differences between pedometer step counts on weekdays versus weekend days (p = 0.755). This contrasts with studies suggesting that children achieve more steps during the week than on the weekend (Brusseau et al, 2011;Tudor-Locke et al, 2009). Our findings could be due to the relatively high income status of the majority of our population, as children from higher income families are more likely to have access to pay-based physical activity opportunities throughout the week and weekend, which is associated with increased physical activity (Sallis et al, 1999(Sallis et al, , 2000.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…While many studies descriptively report physical activity for specific time segments of the day and week, few conduct formal statistical tests of differences in activity between time segments. Previous reviews have compared time-segment-specific physical activity across studies or have limited comparisons of weekdays versus weekends [1619]. Interventions often target particular times of the day, such as school [13, 20], afterschool [12, 21] or recess [22].…”
Section: Introductionmentioning
confidence: 99%
“…The focus of his commentary is "Expected Values for PedometerDetermined Physical Activity in Youth"(Tudor-Locke, McClain, Hart, Sisson, & Washington, 2009). As we indicated in that article, expected values are normative or benchmark values necessary for interpretation and comparison purposes; their use does…”
mentioning
confidence: 99%